European lobbying between transparency and the battle for influence - Mănescu, Dragoș Mihail (Technium Social Sciences Journal, 2021)
Lobbying is regulated at European level by permissive legal provisions but, at the same time, disparate or lacking in legislative and application coherence. The state of the European decision-making process reveals the need to bring about changes that require more rigorous, applied and, why not, severe regulation of lobbying and interest representation.